FUNDAMENTAL INVESTIGATION OF RECYCLED CONCRETE USING PAPER SLUDGE ASH AND SILICA FUME - Rasuli, Mohammad Idris; Shigeishi, Mitsuhiro (MATTER: International Journal of Science and Technology, 2021)
Waste management and recycling of wastages play an important role in having a sustainable city or eco-city. Rapid increasing population in some cities of the world and especially in developing countries cause a different kind of pollution such as air, water, noise, visual, etc. Wastages are directly associated with city contamination. Useful policies for recycling waste can reduce pollution and boost the economy of a country. This study investigates the influence of recycled concrete aggregate (RCA), Silica fume (SF), and paper sludge ash (PSA) on the workability, compressive strength, and acoustic emission behavior of concrete. 5 and 10% of cement were replaced by PSA and silica fume and 10 and 20% of coarse aggregate was replaced by the recycled aggregate. PSA and SF improved the Strength, and acoustic emission behaviors of concrete, moreover, the recycled aggregate also improved the properties of concrete.